The Palestinian public’s attitudes toward the role of cultural programs in television channels in promoting values of communication and cultural dialogue - Al Awadi, Raafat Mohammed Saeed (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to identify the trends of the Palestinian public towards the role of cultural programs in television channels in promoting the values of communication and cultural dialogue from their point of view, and the descriptive analytical approach was used, and the questionnaire was the tool of the study which applied to the sample of the study consisting of (400) researches, selected from the study community to represent a part of the society, they were selected in a random class way from the governorates of Gaza (northern Gaza, Gaza, Central, Khanyounis, Rafah). The results revealed that more than half of the study sample is keen to watch cultural programs presented on television channels by a percentage of (61.2%), and that tv channels that the sample prefer to follow its cultural programs were (Al-Kitab, Falstein Ma‘an, Al-Aqsa, others), The researchers believe that the degree of benefit of exposure to cultural programs in television channels was 43.9%, and the admiration of the sample of the cultural programs presented on television channels came in a percentage of (68.0%), and the results indicated that there is a role for cultural programs In television channels in promoting the values of communication and cultural dialogue on the sample of the study of the Palestinian public reached (51.7%).